2019
DOI: 10.1186/s13068-019-1481-0
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical profiling, prediction of total lipid content and fatty acid profile in oleaginous yeasts by FTIR spectroscopy

Abstract: Background Oleaginous yeasts are considered as a potential lipid source for food, feed and biofuel production. In order to make the yeast-based lipid production environmentally and economically sustainable, there is a need for screening studies in order to find the best yeast lipid producers on different substrates, and to optimize cultivation conditions. Since the target parameter of such screening studies are lipid amounts and profiles, an analytical technique that is able to perform lipid analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 31 publications
(40 reference statements)
5
53
0
Order By: Relevance
“…Genome editing via CRISPR has become routine and is nowadays run in a multiplex manner for many reference strains [132,133]. Fourier-transformed infrared spectroscopy has become a next-generation phenotyping technology to identify fungal strains and their metabolic products [134], while the power of surface analysis tools, such as mass spectrometry-based imaging techniques, has been exploited to identify changes that are brought about by filamentous fungi and their enzymes when they attack and modify insoluble lignocellulose materials [135]. "Ready-touse-microfluidics" have been implemented to study the dynamics of fungal growth and fungal interaction with soil bacteria [136], X-ray microcomputed tomography has been successfully applied to study spatial distribution of hyphae within mycelia and diffuse mass transport therein [137,138], and gene and protein networks have been developed to assist our understanding of filamentous fungal biology holistically [128,139].…”
Section: Improved Tools and Technologies To Study Fungal Biologymentioning
confidence: 99%
“…Genome editing via CRISPR has become routine and is nowadays run in a multiplex manner for many reference strains [132,133]. Fourier-transformed infrared spectroscopy has become a next-generation phenotyping technology to identify fungal strains and their metabolic products [134], while the power of surface analysis tools, such as mass spectrometry-based imaging techniques, has been exploited to identify changes that are brought about by filamentous fungi and their enzymes when they attack and modify insoluble lignocellulose materials [135]. "Ready-touse-microfluidics" have been implemented to study the dynamics of fungal growth and fungal interaction with soil bacteria [136], X-ray microcomputed tomography has been successfully applied to study spatial distribution of hyphae within mycelia and diffuse mass transport therein [137,138], and gene and protein networks have been developed to assist our understanding of filamentous fungal biology holistically [128,139].…”
Section: Improved Tools and Technologies To Study Fungal Biologymentioning
confidence: 99%
“…A direct comparison with previous studies was again not possible since to the best of the authors' knowledge, it is the first time that a model predicting fungal ergosterol content on the basis of acquired spectroscopic data has been presented. Recently, Shapaval et al [62] reported a prediction of the total lipid content in oleaginous yeasts by applying high-throughput FTIR spectroscopy and achieved a high R 2 value for the cross-validation (0.92); however, the R 2 value achieved during the external validation was 0.67. Moreover, the total sterol content in brown algae was estimated with fairly good accuracy but through the use of a single peak of the FTIR spectrum in conjunction with a previously calibrated standard regression line [63].…”
Section: Prediction Of Mushrooms Ergosterol Contentmentioning
confidence: 99%
“…Transmission spectra were acquired for the extracted lipids, FAME mix, and yeast biomass before/after lipid extraction at 120 h of incubation when the highest lipid production was recorded. The peaks assigned to the corresponding functional groups [35] are presented in Table 3 and Fig. 5.…”
Section: Ftir Analysis Of the Yeast Biomass And Extracted Lipid From Swwmentioning
confidence: 99%